2004
DOI: 10.1089/104303404772680029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasmid DNA Removal from Lentiviral Vectors by Benzonase Treatment

Abstract: To improve the purity of lentiviral vector supernatants for clinical studies we have evaluated plasmid DNA removal from lentiviral vectors and also the extent of plasmid DNA associated with transduced CD34 cells in an ex vivo transduction protocol. Optimal conditions of plasmid DNA removal by benzonase treatment were established by varying the temperature, time, and benzonase concentrations in the reaction mix and were determined to be 50 units of benzonase per milliliter of vector supernatant at 37 degrees C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 14 publications
(17 reference statements)
2
55
0
Order By: Relevance
“…However, most of this activity is attributable not to the viral particles themselves but to contaminating tubulovesicular structures, which largely outnumber virions and carry nucleic acids, including the plasmids used in transfection. The observation that TVS carry DNA may account for previous reports of plasmid DNA presence within LV preparations (54) and implies that TVS can activate pathways of innate defense against DNA viruses. Consistent with this notion, we show that TVS induce strong innate responses via a TLR9-dependent pathway and act as adjuvants in vivo for coadministered antigens.…”
Section: Fig 4 Ifn-␣ Induction By LV Preparations and Tvs Is Dependsupporting
confidence: 53%
“…However, most of this activity is attributable not to the viral particles themselves but to contaminating tubulovesicular structures, which largely outnumber virions and carry nucleic acids, including the plasmids used in transfection. The observation that TVS carry DNA may account for previous reports of plasmid DNA presence within LV preparations (54) and implies that TVS can activate pathways of innate defense against DNA viruses. Consistent with this notion, we show that TVS induce strong innate responses via a TLR9-dependent pathway and act as adjuvants in vivo for coadministered antigens.…”
Section: Fig 4 Ifn-␣ Induction By LV Preparations and Tvs Is Dependsupporting
confidence: 53%
“…), clarified by centrifugation for 5 min at 470 ϫ g, and passed through a 0.45-m filter. Virus was treated with 50 U/ml benzonase (Sigma) at 37°C for 20 min to digest contaminating plasmid DNA (40) and then stored at Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown previously that a concentrated and purified LVV product is not required for efficient ex vivo transduction of PBLs at clinical scale (Yang et al, 2008b). In addition, we and others (Sastry et al, 2004) have shown that Benzonase treatment or the presence of residual Benzonase in the vector supernatant does not inhibit the ability of LVV to efficiently transduce lymphoid cells (Fig. 3B-D).…”
Section: Discussionmentioning
confidence: 65%
“…Residual Benzonase was detected by ELISA according to the manufacturer's protocol (EMD Chemicals). Residual lentiviral packaging plasmid DNA was detected by real-time PCR as described previously (Sastry et al, 2004). A standard curve was generated with plasmid pMDLg/pRRE, ranging from 1.0 to 0.0000001 ng.…”
Section: Lentivirus Productionmentioning
confidence: 99%
See 1 more Smart Citation